2014
DOI: 10.1111/anae.12681
|View full text |Cite
|
Sign up to set email alerts
|

Improved non-invasive total haemoglobin measurements after in-vivo adjustment

Abstract: SummaryWe hypothesised that an in-vivo adjustment method and/or a newer sensor would increase the accuracy of non-invasive and continuous haemoglobin monitoring (SpHb) measurements. Two sensors, the R1-25 and R2-25a (the newer version), were used with laboratory total haemoglobin concentration (tHb) values simultaneously recorded. In-vivo adjusted SpHb (AdHb) was calculated by a simple formula: AdHb = SpHb À (1 st SpHb À 1 st tHb). The correlation coefficients between SpHb (or AdHb) and tHb were compared: SpHb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 12 publications
1
12
0
Order By: Relevance
“…SpHb bias (precision) was 0.2 (1.5) g.dl À1 before and À0.7 (1.0) g.dl À1 after retrospective adjustment [11]. In a second study including 19 adult surgical patients requiring 73 measurements, both the bias (0.68 g.dl À1 vs 0.16 g.dl À1 ) and precision (1.02 g.dl À1 vs 0.77 g.dl À1 ) improved after in-vivo adjustment [12]. In this latter study, adjustment was made using haemoglobin concentration measured with an automated gas analyser.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…SpHb bias (precision) was 0.2 (1.5) g.dl À1 before and À0.7 (1.0) g.dl À1 after retrospective adjustment [11]. In a second study including 19 adult surgical patients requiring 73 measurements, both the bias (0.68 g.dl À1 vs 0.16 g.dl À1 ) and precision (1.02 g.dl À1 vs 0.77 g.dl À1 ) improved after in-vivo adjustment [12]. In this latter study, adjustment was made using haemoglobin concentration measured with an automated gas analyser.…”
Section: Discussionmentioning
confidence: 96%
“…) improved after in-vivo adjustment [12]. In this latter study, adjustment was made using haemoglobin concentration measured with an automated gas analyser.…”
mentioning
confidence: 99%
“…Revision of the software to ensure that further freezing during operation of the device could also prevent intra‐patient calibration problems. Results could also be improved using the simple method proposed by Miyashita et al., whereby the difference between the haemoglobin reading from the device and a laboratory or point‐of‐care value is used to adjust subsequent readings on the device (within the same patient) . This method improved the accuracy of non‐invasive haemoglobin measurement in 17 patients (with 71 measurements), but only included those undergoing abdominal surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Miyashita et al have suggested a simple method of in‐vivo calibration (not automatic) which improves both the bias and limits of agreement of the Radical‐7. Masimo has added such a feature, termed ‘in‐vivo adjustment’, which has already received the CE Mark (but not yet FDA approval) and a recently published study appears to confirm this, although the limits of agreement are still in the range −24 to 18 g.l −1 .…”
Section: The Futurementioning
confidence: 99%